Implementation of Dual System Education (DSE) Program in Accounting Expertise Program at SMK PGRI 1 Ponorogo (International Journal of Active Learning, 2019)
The research was carried out at SMK PGRI 1 Ponorogo, Ponorogo Regency, East Java Province. This research aimed to determine the effectiveness of the implementation of the dual system education (DSE) program in the accounting Expertise program at SMK PGRI 1 Ponorogo. There were 9 validators in this research. The results showed that the implementation of the dual education system program in the accounting expertise program at SMK PGRI 1 Ponorogo has not been running effectively as evidenced by the average score of the overall input/planning, process/implementation, and product/assessment of 3.75, while for the effective standard, the scale is 4. The Input/planning stage includes the selection of competencies (4), determination of industry (4.78), preparation of programs (4.78), debriefing of participants (4.78), determination of mentors (4.67). The overall average score is 4.60 â‰¥ 4, so it is said to be effective. The process/implementation stage consists of the preparation of the DSE journal (3.78), DSE monitoring (4), and portfolio documentation (2.78). The overall average score is 3.52 â‰¤ 4, so it is said to be ineffective. The product/assessment stage includes the supervisor assessment (4.11), industry certification (4.78), and score reporting (3.55) with the overall score of 4.14, which is said to be effective.